Ultrasensitive Materials for Electrochemical Biosensor Labels - Koyappayil, Aneesh (Sensors (Basel), 2020)
Since the fabrication of the first electrochemical biosensor by Leland C. Clark in 1956, various labeled and label-free sensors have been reported for the detection of biomolecules. Labels such as nanoparticles, enzymes, Quantum dots, redox-active molecules, low dimensional carbon materials, etc. have been employed for the detection of biomolecules. Because of the absence of cross-reaction and highly selective detection, labeled biosensors are advantageous and preferred over label-free biosensors. The biosensors with labels depend mainly on optical, magnetic, electrical, and mechanical principles. Labels combined with electrochemical techniques resulted in the selective and sensitive determination of biomolecules. The present review focuses on categorizing the advancement and advantages of different labeling methods applied simultaneously with the electrochemical techniques in the past few decades.